3, 6-Anhydro-L-Galactose Dehydrogenase VvAHGD is a Member of a New Aldehyde Dehydrogenase Family and Catalyzes by a Novel Mechanism with Conformational Switch of Two Catalytic Residues Cysteine 282 and Glutamate 248. Issue 7 (27th March 2020) - Wang, Yue; Li, Ping-Yi; Zhang, Yi; Cao, Hai-Yan; Wang, Yan-Jun; Li, Chun-Yang; Wang, Peng; Su, Hai-Nan; Chen, Yin; Chen, Xiu-Lan; Zhang, Yu-Zhong
Abstract: 3, 6-anhydro-α-L -galactose (L-AHG) is one of the main monosaccharide constituents of red macroalgae. In the recently discovered bacterial L-AHG catabolic pathway, L-AHG is first oxidized by a NAD(P) + -dependent dehydrogenase (AHGD), which is a key step of this pathway. However, the catalytic mechanism(s) of AHGDs is still unclear. Here, we identified and characterized an AHGD from marine bacterium Vibrio variabilis JCM 19239 ( Vv AHGD). The NADP + -dependent Vv AHGD could efficiently oxidize L-AHG. Phylogenetic analysis suggested that Vv AHGD and its homologs represent a new aldehyde dehydrogenase (ALDH) family with different substrate preferences from reported ALDH families, named the L-AHGDH family. To explain the catalytic mechanism of Vv AHGD, we solved the structures of Vv AHGD in the apo form and complex with NADP + and modeled its structure with L-AHG. Based on structural, mutational, and biochemical analyses, the cofactor channel and the substrate channel of Vv AHGD are identified, and the key residues involved in the binding of NADP + and L-AHG and the catalysis are revealed. Vv AHGD performs catalysis by controlling the consecutive connection and interruption of the cofactor channel and the substrate channel via the conformational changes of its two catalytic residues Cys282 and Glu248. Comparative analyses of structures and enzyme kinetics revealed that differences in the substrate channels (in shape, size, electrostatic surface, and residue composition) lead to the different substrate preferences of Vv AHGD from other ALDHs. This study on Vv AHGD sheds light on the diversified catalytic mechanisms and evolution of NAD(P) + -dependent ALDHs. Graphical abstract: Image 1 Highlights: 3, 6-anhydro-α-L -galactose (L-AHG) is the main monosaccharide constituent of red macroalgae and metabolized by marine bacteria. AHGDs catalyze the first step of the bacterial L-AHG catabolic pathway with an unknown mechanism. Crystal structures of Vv AHGD were determined in apo and cofactor-bound states. The catalytic mechanism of Vv AHGD is proposed based on structural and mutational analyses. Vv AHGD and its homologs represent a new aldehyde dehydrogenase family.